Problema dan Kebijakan Perumahan di Perkotaan - Sulistiyani, Ambar Teguh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2002)
Providing an adequate housing facilities for the evergrowing urban population is a serious problem. Such problem is easily understood, but has not been succesfully dealth by Indonesian government, as it is purely as a housing problem. Since the root of the problem is urbanization, housing policy should be part of urban management scheme, taking into account all of urban related issues: population density, demographic growth, squatters on slum areas and public facilities In supporting the macro scheme of urban management, there are micro scheme to be implemented